Social Proof as A Leveraging Variable For Purchasing Decisions - Sulistiyani, Endang (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2025)
This study aims to analyze the influence of affiliate marketing and online customer reviews on social proof and purchasing decisions on TikTok. Data collection method by distributing questionnaires to TikTok users in Central Java. The data collection technique uses quota sampling and purposive sampling method. The data analysis method uses structural Equation Modelling, with the AMOS 25 program. The results of the analysis show that the direct and indirect influence between affiliate marketing, online customer reviews on social proof and purchase decisions shows positive and significant results. Social proof is able to strengthen the relationship of the indirect influence of affiliate marketing and online customer reviews on purchasing decisions. This research combines Social Influence Theory and Theory of Planned Behaviour as a bridge to digital strategies in making purchasing decisions. TikTok needs to increase partnerships with affiliate marketers who have a good reputation and great influence in the target market.  Keywords : affiliate marketing, online customer reviews, purchase decisions, social influence theory, theory of planned behaviour